Effect of modified celluloses on dough rheology and microstructure - Correa, María Jimena (2010)
The effect of different modified celluloses on dough microstructure and rheological characteristics was studied. Microcrystalline cellulose (MCC), carboxymethyl cellulose (CMC) and two different types of hydroxypropylmethylcellulose (HPMC F 4M and HPMC F 50) were tested in a range of concentration from 0.25 to 1.5% (flour basis). Doughs were formulated without and with salt (2 % w/w flour basis). Farinographic water absorption increased when hydrocolloids were incorporated and the highest values were obtained in mixtures without NaCl and when HPMCs were added. A linear relationship between the percentage increment in water absorption and the hydrocolloid level was observed within the assayed range of concentrations. The development time was markedly increased when CMC was added. CMC and HPMC did affect or not dough stability depending on the presence or absence of salt whereas the stability was not modified by MCC. Texture attributes and the rheometric parameter tan d were analyzed through Principal Components Analysis (PCA). Two factors described the 88.9% of total variation, one of them composed by hardness, consistency, adhesiveness and tan d and the other composed by resilience and cohesiveness. Hydrocolloids addition softened the dough, particularly when salt was absent. Samples with salt and with hydrocolloids exhibited more cohesive and less resilient characteristics. Rheological results were in agreement with the characteristics of gluten network studied by SEM since a diminished stability and softer dough could be associated with a more disrupted matrix.